Stomalı bireylerde preoperatif ve postoperatif eğitimin öz yeterlilik düzeyi ve peristomal cilt komplikasyonları üzerine etkisi - Çırak, Cansu (My University, 2025)
Amaç: Bu çalışma Stoma ile Yaşam Eğitimi’nin stomalı bireylerde öz yeterlilik düzeyi ve peristomal cilt komplikasyonları üzerine etkisini incelemek amacıyla ön- test son- test kontrol gruplu deneysel araştırma tipinde yapıldı. Gereç ve Yöntem: Araştırma bir şehir hastanesinde genel cerrahi kliniğinde stoma cerrahisi geçiren 81 hastada 01 Temmuz 2023-01Temmuz 2024 tarihleri arasında yapıldı. Veriler Hasta Bilgi Formu, Komplikasyon Değerlendirme Formu, Stoma Öz Yeterlilik Ölçeği kullanılarak toplandı. Kontrol grubundaki bireylere rutin prosedürler uygulanırken, çalışma grubundaki hastalara Stoma ile Yaşam Eğitimi verildi. Bulgular: Taburculuk öncesi, ameliyat sonrası 1. Ay ve 3. Ay ölçümlerinde çalışma grubunda Stoma Bakımı Öz Yeterlilik alt boyut ve Stoma Öz Yeterlilik Ölçeği toplam puanı kontrol grubuna göre anlamlı ölçüde yüksek bulundu (p<0,05). Taburculuk öncesi dönemde çalışma grubunda Sosyal Öz Yeterlilik alt boyut puanı kontrol grubuna göre anlamlı ölçüde yüksek bulunurken (p<0,05), 1. Ay ve 3. Ay ölçümünde fark bulunmadı (p>0,05). Benzer şekilde ameliyat sonrası 1. Ay ve 3. Ay ölçümlerinde çalışma grubunda komplikasyon görülme oranı kontrol grubuna göre daha düşük olmakla birlikte istatistiksel olarak anlamlı fark bulunmadı (p<0,05). Sonuç: Preoperatif dönemde yapılan ve postoperatif dönemde tekrarlanan Stoma ile Yaşam Eğitim kombinasyonunun yalnızca postoperatif dönemde yapılan Stoma ile Yaşam Eğitim’ne göre stoma öz yeterlilik düzeyini arttırmada ve komplikasyon oranını düşürmede etkili bir yöntem olduğu sonucuna varıldı.

Objective: The aim of this study was to examine the effect of Life with a Stoma Education on the Self-efficacy Level and peristomal skin complications in individuals with a stoma through a pre-test post-test controlled experimental research design. Materials and Methods: The study was conducted in a city hospital's general surgery clinic on 81 patients who underwent stoma surgery between July 1, 2023, and July 1, 2024. Data were collected using the Patient Information Form, Complication Assessment Form, and Stoma SelfEfficacy Scale. While routine procedures were applied to individuals in the control group, patients in the experimental group received Life with a Stoma Education. Results: In the measurements taken before discharge, at the 1st month, and at the 3rd month post-surgery, the Stoma Care Self-Efficacy subscale and the total score of the Stoma SelfEfficacy Scale were significantly higher in the experimental group compared to the control group (p<0.05). In the pre-discharge period, the Social Self-Efficacy subscale score was significantly higher in the experimental group than in the control group (p<0.05), but no significant difference was found in the measurements at the 1st and 3rd months (p>0.05). Similarly, although the complication rate was lower in the experimental group than in the control group at the 1st and 3rd months post-surgery, the difference was not statistically significant (p>0.05). Conclusion: It was concluded that the combination of Life with a Stoma Education provided in the preoperative period and repeated in the postoperative period is a more effective method in increasing stoma Self-Efficacy levels and reducing complication rates compared to Life with a Stoma Education provided only in the postoperative period.
The effect of preoperative and postoperative education on stoma self efficacy scale and peristomal skin complications in individuals with in
Keywords: Hemşirelik; Nursing; peristomal complications; peristomal komplikasyon; Preoperatif eğitim; Preoperative education; stoma bakımı; stoma care; stoma öz; stoma self-efficacy; yeterlilik